Novel compact waveguide filtering twist for computer numerical control machining. Issue 1 (8th December 2022) - Zhang, Yi; Shang, Xiaobang; Xu, Jun; Guo, Yuewei; Duan, Lei; Lu, Xiao
Abstract: In this letter, the authors present a novel compact waveguide filtering twist that can be readily fabricated from metal using the computer numerical control (CNC) machining process. This filtering twist comprises four coupled resonators that are rotationally deformed to provide the desired 90° twist. Such resonator structures eliminate the use of curved features and therefore are ideally suitable for conventional CNC machining. The proposed design offers appealing advantages, including great compactness, easy fabrication, and good scalability to millimetre‐wave and terahertz frequencies. The design is demonstrated at X‐band and has a fourth‐order Chebyshev filter response (bandwidth 0.4 GHz, centred at 10 GHz). The good agreement between simulation and measurement results validates the proposed concept. Abstract : A novel compact waveguide filtering twist can be readily fabricated from metal using the computer numerical control (CNC) machining process. This filtering twist is comprised of four coupled resonators which are rotationally deformed to provide the desired 90° twist.